The effect of physical activity on life satisfaction among sports science students: a moderated mediation model of resilience and mindfulness - Secer, Emrah; Kacay, Zulbiye; Yildiz, Nuh Osman; Talaghir, Laurentiu-Gabriel; Cosoreanu, Dumitru Marius; Bentea, Cristina Corina (Frontiers in Psychology, 2025)
BackgroundThis study examines the effect of physical activity (PA) on life satisfaction (LS), focusing on the mediating role of psychological resilience (PR) and the moderating role of mindfulness (MF).MethodParticipants were 363 sports science students (240 male and 123 female). Data were collected through International Physical Activity Questionnaire-Short Form, the Life Satisfaction Scale, the Psychological Resilience Scale-Short Form and the Mindfulness Scale. The measurement model was tested using confirmatory factor analysis (CFA) in AMOS 21 and hypothesis were analyzed using Hayes’ (2022) Process Macro models (4, 1, and 7).ResultsThe mediation effect (Model 4) indicated that the indirect effect of PA on LS through PR was significant. The moderation analysis (Model 1) showed that mindfulness significantly moderated the relationship between PA and PR. Finally, the moderated mediation model (Model 7) confirmed that the indirect effect of PA on LS via PR was stronger at higher levels of mindfulness. Although the effect size was small, it highlights the practical importance of integrating mindfulness in resilience pathways.ConclusionThese findings suggest that physical activity contributes to life satisfaction by enhancing resilience, and that this indirect effect is conditioned by mindfulness. These findings point to the potential value of resilience-building and mindfulness-based programs in educational and psychological practice. However, as the study sample consisted of sports science students from a single faculty, the results should be interpreted with caution regarding generalizability.